2017
DOI: 10.18632/oncotarget.21583
|View full text |Cite
|
Sign up to set email alerts
|

SETD7 is a prognosis predicting factor of breast cancer and regulates redox homeostasis

Abstract: SETD7 is a methyltransferase that specifically catalyzes the monomethylation of lysine 4 on histone H3. A variety of studies has revealed the role of SETD7 in posttranslational modifications of non-histone proteins. However, the prognostic value of SETD7 on breast cancer and the ability of SETD7 of regulating intrinsic redox homeostasis has never been investigated. In this study, using The Cancer Genome Atlas (TCGA) database, we revealed that SETD7 was a potential prognostic marker of breast cancer. Median sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…For instance, Chen et al revealed that SETD7 overexpression induced HCC cell proliferation, whereas SETD7 knockdown suppressed HCC cell proliferation [31]. Huang et al demonstrated that SETD7 induced breast cancer cell proliferation and suppressed cell apoptosis, which suggested that SETD7 expression level can predict the prognosis of breast cancer [32]. Here, we found that overexpression of SETD7 promoted PTC cell proliferation and inhibited apoptosis, whereas the downregulation of SETD7 had opposite effects on PTC cells.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, Chen et al revealed that SETD7 overexpression induced HCC cell proliferation, whereas SETD7 knockdown suppressed HCC cell proliferation [31]. Huang et al demonstrated that SETD7 induced breast cancer cell proliferation and suppressed cell apoptosis, which suggested that SETD7 expression level can predict the prognosis of breast cancer [32]. Here, we found that overexpression of SETD7 promoted PTC cell proliferation and inhibited apoptosis, whereas the downregulation of SETD7 had opposite effects on PTC cells.…”
Section: Discussionsupporting
confidence: 53%
“…SETD7 (also known as SET7/9) is a 41 kDa lysine-specific SET-domain methyltransferase, which is the only lysine methyltransferases (KMT)7 family member due to its unique enzymatic activity and protein domain architecture [ 23 ]. Recent investigations indicated that SETD7 is potentially a biomarker for hepatocellular cancer [ 24 ] and breast cancer [ 25 , 26 ], although the role of SETD7 in breast cancer is controversial [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…SETD7 is the only lysine methyltransferases seven family members which can methylate transcription factors [31]. SETD7 could be used as a prognostic indicator for breast cancer, downregulation of it suppressed expression of antioxidant enzymes and destabilized the redox status [32]. SETD7 and ISL1 may combine to form a complex on the ZEB1 promoter to promote tumorigenesis in GC cells [33].…”
Section: Discussionmentioning
confidence: 99%